Origins of Dystopian novel and its peculiarities shown in Herbert Well’s ''The Sleeper Awakes'' and Aldous Huxley's ''Brave New World'' - Shapsanova Feruza Muzaffarovna; Mansurxadjayeva Madina Toirjon qizi (Genius Journals, 2022)
In this article, the author analyzes renowned dystopian novels, “Brave New World” by Aldous Huxley, and “The Sleeper Awakes” by the writer who gained fame for his science fiction novels, Herbert Wells. Dystopian type of a novel controversy to the notion “Utopia”. It tells a story of collapsing imagination about the ideal world or the ideal future society. The purpose of the article is to delve into the origins of dystopian type of novelty and penetrate through dystopian novels to its ideas, intentions, and moral conclusions. The creators of dystopian novels, Herbert Wells and Aldous Huxley, whose works we are going to analyze were contemporary English writers of the 20th century. They were very prolific writers, the authors of many famous works about the future society or being more exactly about “the dark side of the paradise-like world, Utopia”
Keywords: Utopia; Dystopia; Morality; Communism